The role of the TCC in the training of the research-teacher: the case of the license graduation in geography of the IFRN - Saraiva Junior, João Correia (Revista Ensino de Geografia (Recife), 2021)
The production stage of the Graduation Conclusion Paper (TCC) is highlighted by several challenges that play an important role in the creation and / or development of researchers. In undergraduate license courses, developing research in the form of TCC is a task that faces the challenges of research-teacher training. The general objective of this article is to discuss the role of the Graduation Conclusion Paper in the training of future professionals in geographic education, having as a case study the IFRN Graduation license in Geography. The methodology is based on conceptual review, application of questionnaires and synthesis of the collected data. Having analyzed the data, the results indicate that, in the IFRN Graduation license in Geography, the impacts of the TCC production have been positive in the training of research-teachers, although there are obstacles that need attention, mainly, of the teaching staff in the generation an environment conducive to the construction of knowledge in a collaborative way.